2011
DOI: 10.15835/nbha3916081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Metal from Polluted Soils on the Rhizobium Diversity

Abstract: Heavy metals adversely influence microorganisms, affecting their growth, abundance, genetic diversity, nodulation ability and efficacy. The aim of this study was to isolate and characterize free-leaving Rhizobium from soil which were artificially polluted with Cu (100, 250, and 500 mg kg-1 soil), Zn (300, 700, and 1500 mg kg-1 soil) and Pb (50, 250, and 1000 mg kg-1 soil), but also with a mixture of all these metals, and cultivated with red clover (Trifolium pratense L.), and to compare them with bacteria isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Reductions in bacterial counts of Rhizobium sp. have been reported with the increasing concentrations of heavy metals such as Cu, Zn and Pb, either sole or in combinations, and variations in the expression of symbiotic genes including nod genes (Stan et al 2011 ).…”
Section: Abiotic Stress Resistance Of Rhizobiamentioning
confidence: 99%
“…Reductions in bacterial counts of Rhizobium sp. have been reported with the increasing concentrations of heavy metals such as Cu, Zn and Pb, either sole or in combinations, and variations in the expression of symbiotic genes including nod genes (Stan et al 2011 ).…”
Section: Abiotic Stress Resistance Of Rhizobiamentioning
confidence: 99%
“…Elevated metal concentrations influence microbial populations by affecting their growth, abundance, diversity (11)(12)(13), and activity (14). Metals exert selection pressure on microorganisms, resulting in the emergence of microbial populations with a higher tolerance to metals but with a lower diversity compared to that of unpolluted neighboring areas (11,15,16).…”
mentioning
confidence: 99%
“…It has been showed that with the elevated concentrations of heavy metals such as copper, zinc, and lead, the numbers of nitrogen fixing organisms like Rhizobium sp . cells are decreased and also their nod genes expression are interrupted . Moreover, it was suggested that the soil content of microbial biomass and their activity are used as good indicators for the level of heavy metals‐contaminated soil .…”
Section: Introductionmentioning
confidence: 99%